Rumah Puan Milah Binti Muda, Kampung Simpang Krayong, Jasin, Melaka [lukisan teknik] - Mohd. Daniel Iman Mohd. Delan; Muhammad Faizal Jamaluddin; Mohd. Rizal Abdul Rahim; Wan Osman Wan Harun; Noor Hidayah Rosli; Nurlina Azrin Abdul Rahim (Skudai : Universiti Teknologi Malaysia, 1999)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti Teknologi Malaysia, 1999